Significance of Testing Anti-HBcIgM Antibodies for the Screening of Hepatitis B in the Donor Blood. - Mehmood, Asif; Raja, Arsalan Jamil; Rasool, Shafqat; Haque, Israr ul; Nabi Tayyab, Ghias Un (Journal of Ayub Medical College Abbottabad, 2021)
Background: The purpose to perform this study was to screen blood donors for possible occult HBV by checking the seroprevalence of the hepatitis B antibodies in blood donors. It was a Cross-sectional study conducted at Blood Bank of Lahore General Hospital Lahore from April to June 2015 (3-months). Methods: In this prospective study, 180 healthy blood donors, presenting to the blood bank of Lahore General Hospital were selected. Their detailed demographic data and blood samples were collected. HBsAg testing was done by ELISA and further HBc IgM testing was also done by ELISA. Those testing positive for HBc IgM were further evaluated by real-time PCR to detect HBV DNA. Results: Mean duration of the life span was 26.51 years with a range of 18-61 years. Sex distribution show 93.9% (n=169) males and 6.1% (n=11) females. HBsAg was positive in 3.3% (n=6) while their HBc IgM was negative and HBc IGM was positive in 2.2% (n=4) of the healthy donors in whom HBsAg was found negative by ICT method. further qualitative HBV DNA by rt-PCR was done on those positive with anti HBc IgM and no patient had HBV DNA detected from their blood. Conclusion: Without routine screening of the sera for the HBc Antibody, the low-level HBV viraemia may not be detected as the nonappearance of the surface antigen in the blood of apparently healthy donors do not ensure the absence of circulating virus in the blood of these donors. Keywords: Blood Donors; Hepatitis B virus; Screening